Historiography and Identity I: Ancient and Early Christian Narratives of Community - Pohl, Walter (Cultural Encounters in Late Antiquity and the Middle Ages, 2019)
The six-volume sub-series Historiography and Identity unites a wide variety of case studies from Antiquity to the Late Middle Ages, from the Latin West to the emerging polities in Northern and Eastern Europe, and also incorporates a Eurasian perspective which includes the Islamic World and China. The series aims to develop a critical methodology that harnesses the potential of identity studies to enhance our understanding of the construction and impact of historiography.This first volume in the Historiography and Identity sub-series examines the many ways in which historiographical works shaped identities in ancient and medieval societies by focusing on the historians of ancient Greece and the late Roman Empire. It presents in-depth studies about how history writing could create a sense of community, thereby shedding light on the links between authorial strategies, processes of identification, and cultural memory. The contributions explore the importance of regional, ethnic, cultural, and imperial identities